VAKSIN FLU BURUNG DI MANUSIA SEBAGAI UPAYA ALTERNATIF PENCEGAHAN TERHADAP RE-EMERGING VIRUS H5N1 - Ratih Dian Saraswati; Risqa Novita (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2021)
A total of 182 human cases of avian influenza have been reported in Indonesia in the period 2004-2011, with a case fatality rate (CFR) among them of 86%. Various risk factors for avian influenza transmission have also been identified, including a high population, having many types of poultry (broiler, layer, village chickens, etc), traditional poultry systems that promote close human relationships, and the presence of several areas in Indonesia which are strategic locations as a place to rest and meet various wild birds. Vaccination is one of the efforts to prevent the re-emergence of H5N1 avian influenza transmission. However, the avian influenza vaccine for the public is not yet available in Indonesia. The purpose of this review article is to examine the avian influenza vaccine in humans as a preventive measure against the re-emergence of avian influenza in Indonesia, and to determine the progress of developing avian influenza vaccines. The results of the review show that several avian influenza vaccine candidates have been approved by WHO, one of which is a vaccine candidate using an isolated virus from Indonesia. This information on the development of avian influenza vaccines for humans is useful and can be used as an avian influenza pre-pandemic preparedness in Indonesia. Abstrak Sebanyak 182 kasus flu burung pada manusia telah dilaporkan di Indonesia pada periode tahun 2004-2011, dengan case fatality rate (CFR) sebesar 86%. Berbagai faktor risiko penularan flu burung juga telah diidentifikasi, antara lain jumlah penduduk yang tinggi, memiliki banyak jenis unggas (ayam broiler, layer, kampong, dsb), sistem perunggasan tradisional yang membuat kedekatan hubungan antara manusia, dan adanya beberpa wilayah di Indonesia yang menjadi lokasi strategis sebagai tempat istirahat dan bertemunya berbagai unggas liar. Vaksinasi merupakan salah satu upaya untuk mencegah munculnya kembali penularan flu burung H5N1. Namun demikian, vaksin flu burung untuk masyarakat belum tersedia hingga saat ini. Tujuan dari review artikel ini adalah untuk mengkaji vaksin flu burung pada manusia sebagai tindakan pencegahan terhadap kemunculan kembali flu burung di Indonesia, dan untuk mengetahui kemajuan pengembangan vaksin flu burung. Hasil review menunjukkan beberapa kandidat vaksin flu burung telah disetujui oleh WHO, salah satunya adalah kandidat vaksin menggunakan isolat virus asal Indonesia. Informasi perkembangan vaksin flu burung bagi manusia ini bermanfaat dan dapat digunakan sebagai kesiapsiagaan prepandemi flu burung di Indonesia.